PENGEMBANGAN PERANGKAT PMR DAN PENGARUHNYA TERHADAP HASIL BELAJAR MATEMATIKA PADA SISWA KELAS VIII SMP KATOLIK AMBON - Mataheru, Helena (Jurnal Magister Pendidikan Matematika (JUMADIKA), 2020)
This study aimed at: 1) producing a valid learning material of realistic mathematic for flat space solid edge material at VIII grade students of SMP Katolik Ambon; 2) finding out the effect of using learning material of mathematic realistic toward learning outcome for flat space solid edge material at VIII grade students of SMP Katolik Ambon. This study was an experiment research initialized by conducting development research to produce learning material oriented to realistic mathematic learning for flat space solid edge material at VIII grade. The development process of learning material followed the procedure of Thiagarajan 4-D model of development that had been modified without dissemination. The results of learning material development with realistic mathematic learning approach were lesson plan, learning material, students’ worksheet and learning outcome test, while the experiment was used to describe the learning effectiveness with realistic mathematic learning approach and to compare learning outcome between students who followed learning process with realistic mathematic learning approach and students who learnt conventionally for flat space solid edge material. The results showed that: 1) learning material with realistic mathematic learning approach for flat space solid edge material had fulfilled the criteria which was show by good expert validation, teachers’ activity in managing learning process, students’ activity, positive responses of teachers and students toward learning material and the average percentage of students learning outcome achieving 79% of whole students in the class; 2) students learning outcome was increased based on analysis of inferential statistic, so it could be concluded that the development of learning material of realistic mathematic affected students learning outcome for flat space solid edge material at VIII grade students of SMP Katolik Ambon